Lucky turtle : a novel - Roorbach, Bill (Algonquin Books of Chapel Hill, 2022)
"When privileged white sixteen-year-old Cindra is sent to a reform camp in Montana, she becomes transfixed by Lucky, a mysterious camp employee. As the connection between them grows, Lucky and Cindra become lovers and escape into the Rocky Mountains to create an idyllic life, living off Lucky's vast knowledge of the wilderness. But they can run from the outside world for only so long, and the consequences of their naïve fantasy of a future together will keep them apart for decades. Lucky goes to prison, and Cindra becomes trapped in a relationship where she is controlled and defined by a man who claims to be her rescuer. For Cindra, there will never be another Lucky, and she dreams of one day finding him, the only man she's ever fully trusted, her soulmate"--